2023
DOI: 10.14744/tjtes.2023.96554
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the prognostic role of systemic immunoinflammatory index in patients with acute pancreatitis

Abstract: BACKGROUND:The aim of this study was to examine the effect of systemic immunoinflammatory index (SII), calculated on presentation to the emergency department (ED), on the prediction of clinical outcomes of patients who were diagnosed with acute pancreatitis (AP). METHODS:This research was designed as a single-center, cross-sectional, and retrospective study. Adult patients who were diagnosed with AP in the ED between October 2021 and October 2022 in the tertiary care hospital, whose diagnostic and therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…[6] Furthermore, including this study, many studies in the literature have demonstrated that an increase in leukocyte count is significant in diagnosing AA in pregnant patients. [10][11][12] However, WBC is not an appendicitis-specific parameter and is elevated in many inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Furthermore, including this study, many studies in the literature have demonstrated that an increase in leukocyte count is significant in diagnosing AA in pregnant patients. [10][11][12] However, WBC is not an appendicitis-specific parameter and is elevated in many inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Another parameter used in the evaluation of systemic inflammation is the Systemic Inflammatory Index (SII), and it is also an important index used in the follow-up of many diseases. [10,11] Considering that the delay in the diagnosis of AA may have a mortal course for both the fetus and the mother, the importance of correct diagnosis and timely intervention becomes even more evident. However, it is also important to avoid unnecessary or delayed surgery of AA in pregnant women.…”
mentioning
confidence: 99%
“…SII is a comprehensive in ammatory index introduced in recent years, and it can more comprehensively re ect the in ammatory and immune balance state of the disease than NLR, PLR, and neutrophil and lymphocyte counts [15,16] .In our study, the incidence of PEP was higher in patients in the high SII group.Meanwhile, related studies show that high levels of SII can predict the severity of acute pancreatitis [17] .The use of SII in pancreatic diseases was further expanded after rst providing its clinical reference signi cance by Gerd Jomrich et al [18] .The measurement of SII is helpful in predicting the clinical outcome of acute pancreatitis, as observed by Dalkılınc Hokenek U et al [19] .It is well known that the in ammatory response is closely associated with the occurrence and development of pancreatitis.Neutrophils and reactive oxygen species (ROS) cooperate to promote the process of pancreatitis [20] .Excessive recruitment and activated neutrophils cause an extensive cascade of chemokine and cytokines, leading to the progression of pancreatic acinar cell damage and imbalance of tissue immunity [21,22] .Lymphocytes are implicated in regulating pathways of the immune system, which apoptosis and redistribution lead to lymphopenia, resulting in an immune imbalance regulating pancreatitis.Large amounts of oxygen free radicals and proteolytic enzymes may damage the pancreatic vascular endothelial cells, which can then cause platelet aggregation, activate the blood-coagulation cascade, and ultimately lead to the in ammatory cascade.SII re ects both hyperactive coagulation and in ammatory pathways, which are underlying mechanisms of PEP.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical severity of AP can progress from a localized, self-limiting condition to multi-organ failure, sepsis, and death. [ 1 - 3 ] While the incidence of mortality due to AP is 1% in general, the mortality rate can reach 40% in patients who are hospitalized and develop organ failure. [ 4 ] Thus, early diagnosis of AP patients who will require critical care is important.…”
Section: Introductionmentioning
confidence: 99%